Safety and acute clinical outcomes of atrial fibrillation catheter ablation in octogenarians: a multicentre evaluation with a matched younger cohort. (24th May 2021) - Karim, N; Kozhuharov, N; Jarman, J; Furniss, S; Veasey, R; Ullah, W; Vouliotis, A-I; Martin, C; Kalla, M; Osmanagic, A; Ginks, M; Pope, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: Sven Knecht and the International Octogenarian AF ablation group Background: Octogenarians are a fast-growing demographic with a high burden of atrial fibrillation (AF). There are limited data on procedural safety and acute outcomes of catheter ablation (CA) for AF in this group. Purpose: Investigation of complications & outcomes in octogenarians undergoing CA for AF. Methods: Data on all octogenarian patients who underwent AF ablation at nine European cardiology centres between 2013 and 2019 were retrospectively analysed and matched with control patients aged <80 years. The characteristics used for matching were type of AF, type of procedure (de novo or redo), & the year of procedure. Results: 216 octogenarians (81.9 ± 1.9 years; 52.8% females) underwent an AF ablation procedure, and were matched with 216 patients aged <80 years (62.4 ± 9.5 years, 34.7% females), p <0.001 for both. The proportion of paroxysmal and persistent AF was 43.5% & 56.5% respectively in both groups, and 79.3% of the procedures were de novo. RF ablation made up 75.4% & 75.9% (p = 0.90) procedures in octogenarians and controls respectively. 17 complications occurred in 14 (7.9%) octogenarian patients and 11 in 11 (5.1%) patients in the younger matched cohort (p = 0.07). There were 4.2% & 1.9% major complications (p= 0.17) and 3.7% & 3.2% minor complications (p= 0.77) in the octogenarian & younger cohorts respectively. Complications in octogenarians consisted of groin complications (n = 6), pneumonia (n = 3), pericardial effusion (n = 2), phrenic nerve injury (n = 2), pulmonary oedema (n = 1), gastroparesis (n = 1), stroke (n = 1). Acute procedural success rates were 99.1% & 99.5% (p = 0.62) The complication rates were similar for RF; 6.0% vs 5.4% (p = 0.79) and Cryoballoon; 14.0% vs 4.1% (p = 0.09) in both octogenarians and younger cohort respectively. Conclusion: In spite of significantly higher overall risk profile of octogenarians undergoing AF ablation, there is no difference in acute procedural success and complication rates as compared to younger patients